2016
DOI: 10.1038/ncomms13948
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast electronic response of graphene to a strong and localized electric field

Abstract: The way conduction electrons respond to ultrafast external perturbations in low dimensional materials is at the core of the design of future devices for (opto)electronics, photodetection and spintronics. Highly charged ions provide a tool for probing the electronic response of solids to extremely strong electric fields localized down to nanometre-sized areas. With ion transmission times in the order of femtoseconds, we can directly probe the local electronic dynamics of an ultrathin foil on this timescale. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 48 publications
7
141
0
2
Order By: Relevance
“…A key drawback toward their elucidation via the data presented in Figures 1–5 is however that the lattice of the supporting graphene is not resolved in these images due to nonoptimal imaging conditions for the lighter carbon ( Z C = 6) as well as static residual adventitious carbon contamination which is typical 5,36,68 for graphene samples from sample transport and storage in air. This precludes the assessment of orientational relations between the underlying graphene and the crystallizing MoS 2 in Figures 1–4, despite the interesting observation that after 17 min electron beam exposure, the FT in Figure 1b shows signs of one discrete hexagonal spot pattern across several nonconnected MoS 2 crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…A key drawback toward their elucidation via the data presented in Figures 1–5 is however that the lattice of the supporting graphene is not resolved in these images due to nonoptimal imaging conditions for the lighter carbon ( Z C = 6) as well as static residual adventitious carbon contamination which is typical 5,36,68 for graphene samples from sample transport and storage in air. This precludes the assessment of orientational relations between the underlying graphene and the crystallizing MoS 2 in Figures 1–4, despite the interesting observation that after 17 min electron beam exposure, the FT in Figure 1b shows signs of one discrete hexagonal spot pattern across several nonconnected MoS 2 crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…Recent experimental work showed that heavy ions, especially in high initial charge states, undergo ultrafast neutralization and de-excitation within less than 10 fs when transmitted through a freestanding monolayer of graphene 23 or 1 nm thick polymeric carbon nanomembranes 24 . The neutralization is accompanied by a strong enhancement of the ion stopping 25 , which depends on both, the ion incident charge state Q in and the amount of charge exchange ΔQ = Q in − Q out .…”
mentioning
confidence: 99%
“…of velocity), the energy loss in graphene predicted for by F. Mao is around 11 eV/Å, meanwhile, Echenique gives 3.3 eV/Å. Also, recent experiments of slow highly charged ions interacting with graphene layers report that the energy loss and charge exchange of ions in two-dimensional materials show significant differences with respect to bulk solids (24,25). The high energy losses differ by an order of magnitude with respect to results obtained by TRIM (12).…”
Section: Resultsmentioning
confidence: 97%
“…Q11 The higher energy loss for protons, found in our experiments and which recent calculations would fairly explain, can be traced to the unusual properties of graphene. Assuming that the measured energy loss is due to electronic excitations, and graphene with a high electron mobility can react very fast to the presence of the intruder, near the surface, with its subsequent fast screening (25). This phenomenon produces a very high and fast flux of electrons against the energetic proton producing a high momentum transfer which translates into a high graphene stopping power on the particle.…”
Section: Resultsmentioning
confidence: 99%